Recurrent uterine artery pseudo-aneurysm requiring repeat embolization during pregnancy - A case report - Astrid Mulkers; Kathleen Podevyn; Isabelle Dehaene (Elsevier, 2021)
Background: Uterine artery pseudo-aneurysms (UAP) mainly occur after traumatic delivery or traumatic pregnancy termination. A UAP can be either asymptomatic or present with symptoms such as vaginal bleeding, abdominal pain, hypovolemic shock, or fever when infected. We describe a patient diagnosed with a uterine artery pseudo-aneurysm in pregnancy that required repeat embolization. The patient had no risk factors in her recent medical history. She did, however, undergo in-vitro fertilization with oocyte retrieval performed under transvaginal ultrasonographic guidance. We suggest the hypothesis of formation of the pseudo-aneurysm secondary to vascular injury during oocyte retrieval. Case Report: A 35-year-old primigravida, who conceived by in-vitro fertilization, presenting with severe abdominal pain at 19 2/7 weeks of gestation. Ultrasound examination with color doppler imaging revealed a hypo-echoic lesion with turbulent arterial flow pattern on the lower left side of the uterus. Selective catheterization and subtraction angiography permitted diagnosis of a large pseudo-aneurysm of the left uterine artery. A selective embolization was performed. Recanalization of the embolized artery was confirmed 11 weeks after initial presentation, requiring repeat embolization. A planned caesarean section was performed at 34 weeks of gestation and a healthy boy was born with a birth weight of 2065 g. Conclusion: Uterine artery pseudo-aneurysm is a rare but potentially life-threatening condition. It can be diagnosed using (doppler) ultrasound, revealing a hypoechoic mass with swirling blood flow. Angiography is the standard reference in diagnosing UAP and may provide definitive treatment. Management with selective unilateral uterine artery embolization appears to be safe in hemodynamically stable patients. It does not compromise uteroplacental circulation and may help to prolong the pregnancy, reducing morbidity associated with preterm birth.